GREAT OF NECESSITIES OF COUNTRIES ECONOMICS IN THE RESOURCES OF BOWEL ON THE EARTH - BODIUK, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Analysis of publications is conducted from the problems of the use of bowels of the earth. Determination of concept vehicle of global necessities of economies of countries is given. The concepts of globalization of geological survey requirements are grounded. Researches of dynamics and pattern of requirements of economies of countries are actual for economic geology.